Implementation of Brigade Kupang Sehat Policy in Reducing Maternal and Child Mortality Ratio in Kupang City - Try Sutyo Sanjaya Pali; Yoseph Kenjam; Rina Waty Sirait (Universitas Nusa Cendana, 2022)
Brigade Kupang Sehat (BKS) is a program of the Kupang City Health Office specifically providing emergency services to all residents of Kupang City for free for 24 hours. The purpose of this study was to determine the implementation of BKS policy in reducing maternal and child mortality in Kupang City. The method used in this research was qualitative. Data were collected by interview. Four informants were selected by applying purposive sampling technique. The results showed that BKS has an emergency program to help reduce maternal and child mortality. BKS provided medical equipment, transportation/ambulance equipped with a midwife kit, response time, pregnancy check-ups, and postpartum services including family planning services after giving birth, collaboration with public health center and hospitals for referral process, and socialization about the function and role of BKS. Obstacles experienced by BKS included economic factors and a lack of knowledge in pregnant women in choosing a place of delivery. BKS also noted that pregnant women had a complete opening at home, had no pink books or MCH, refusal from pregnant women or families to be referred to better health facilities. The socialization of BKS is needed to increase the awareness of residents of its services, especially for those with low income.